2021
DOI: 10.3221/igf-esis.57.11
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure and Mechanical Properties of Aluminum Cast Alloy A356 reinforced with Dual-Size B4C Particles

Abstract: The paper details the studies carried out on a dual-size particulate composite prepared by stir casting using A 356 aluminum alloy and B4C powders. Three composite compositions, viz., A356 plus 2% B4C (44µm size and 105µm size in 1:1 ratio), 4% B4C (3:1 ratio), and 6% B4C (1:3 ratio) were cast in finger molds, from which test specimens were prepared for hardness and tensile tests as well as for metallography. Vickers hardness tests, tensile tests and microstructure analysis using an optical microscope were con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…From the graph, it is observed that, the increasing TiB 2 and CeO 2 particulates content in Al-6061, marginally reduces the ductility in ascast and hot rolled composites [44,45]. When compared to ascast material, it is found that the hot rolled matrix and its MMCs show improved ductility.…”
Section: Tensile Strengthmentioning
confidence: 96%
“…From the graph, it is observed that, the increasing TiB 2 and CeO 2 particulates content in Al-6061, marginally reduces the ductility in ascast and hot rolled composites [44,45]. When compared to ascast material, it is found that the hot rolled matrix and its MMCs show improved ductility.…”
Section: Tensile Strengthmentioning
confidence: 96%
“…However, it was still higher than that of the single-reinforcement composite (Al/B 4 C). In continuation, Chandrashekar et al [ 96 ] also incorporated dual-sized B 4 C powders, namely, 44 µm and 105 µm sizes, in A356 alloy by using the stir-casting method. It was observed that the higher content of B 4 C powders in the dual-particle-size composites will increase their tensile strength and hardness by up to 35% and 15%, respectively.…”
Section: Mechanical and Tribological Properties Of Al-based Mmcsmentioning
confidence: 99%
“…Aluminum, due to its non-toxicity, high thermal conductivity, low density, remarkable corrosion resistance, and ease of formation, casting, and machining, finds extensive applications [10][11][12]. The metal's non-sparking and nonmagnetic characteristics, along with being the sixth most ductile and the second most malleable, add to its widespread usage [13].…”
Section: Introductionmentioning
confidence: 99%